Pelatihan Penggunaan GPS Untuk Pemetaan Wilayah di Desa Kuluk Bali, Kabupaten Katingan, Kalimantan Tengah - Neny Fidayanti; I Putu Putrawiyanta; Noveriady; Novalisae; Ferdinandus (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2023)
Kuluk Bali Village has the authority to regulate and manage government affairs, regional affairs and community interests based on customary law, customary rights and community initiatives which are recognized and respected in the government system of the unitary state of the Republic of Indonesia. Mastery of technology in the field of regional mapping is part of the need for village officials and the community to know and protect their rights, such as village territorial boundaries and also community rights over their ownership areas, for example community gardens and other forms of managed land. The community's need to map their managed areas and the limited knowledge of the community in mapping areas are the basis for carrying out training activities on the use of GPS. The training aims to improve knowledge and skills, especially for Kuluk Bali village officials to become superior human resources in mastering technology, one of which is GPS. The training method is carried out by providing lectures, practical assistance and discussions. The training provides knowledge for village officials and communities to operate GPS, so that they can independently determine village boundaries and coordinate points for their management areas.